Social And Cultural Context Analysis Of Taxpayer Compliance Behavior Of Msme Actors - Riyanto, Didik; Rasyid, Aliy; Juliyanti, Agnia (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2025)
This study aims to analyze the extent to which social and cultural contexts influence the tax compliance behavior of Micro, Small, and Medium Enterprises (MSMEs) in Rengasdengklok District. The research is motivated by national survey findings indicating low tax contributions from the MSME sector, often associated with limited awareness and understanding of tax obligations despite various government incentives and simplified services. This research employed a quantitative approach using primary data collected through structured questionnaires distributed to MSMEs operating in Rengasdengklok District. The sample was selected using purposive sampling based on the study's relevant criteria. Data analysis included classical assumption tests and multiple regression analysis to assess the effects of the social and cultural context variables on tax compliance. The results indicate that the social context, measured by descriptive, subjective, deferral, and personal norms, positively influences tax compliance among MSMEs. Likewise, cultural context variables also demonstrate a positive and significant impact on MSME tax compliance in the studied area. This study provides empirical evidence on how social norms and cultural characteristics shape tax compliance behavior within local MSME communities. The findings enrich the behavioral tax compliance literature in the Indonesian context and offer practical insights for policymakers to design more culturally aligned approaches to improve MSME tax compliance.